Metaphorical Conceptualizations (Inter)Cultural Perspectives - Schröder, Ulrike; Mendes de Oliveira, Milene; Tenuta, Adriana Maria (Applications of Cognitive Linguistics [ACL] ;, 2022)
Honorary editor: René Dirven The series Applications of Cognitive Linguistics (ACL) welcomes book proposals from any domain where the theoretical insights developed in Cognitive Linguistics (CL) have been (or could be) fruitfully applied. In the past thirty-five years, the CL movement has articulated a rich and satisfying view of language around a small number of foundational principles. The first one argues that language faculties do not constitute a separate module of cognition, but emerge as specialized uses of more general cognitive abilities. The second principle emphasises the symbolic f.